2013
DOI: 10.1098/rsif.2013.0527
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the efficacy of hyperthermia treatment

Abstract: Multimodal oncological strategies which combine chemotherapy or radiotherapy with hyperthermia, have a potential of improving the efficacy of the non-surgical methods of cancer treatment. Hyperthermia engages the heat-shock response (HSR) mechanism, the main component of which are heat-shock proteins. Cancer cells have already partially activated HSR, thereby hyperthermia may be more toxic to them relative to normal cells. On the other hand, HSR triggers thermotolerance, i.e. hyperthermia-treated cells show an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…It has been widely reported that tumor cells can activate the cytoprotective and antiapoptotic pathways like heat shock response, thus leading to thermoresistance to oppose PTT and survive. The subsequent heat shock response could directly lead to stressful overexpression of heat shock proteins (HSPs) including HSP110, HSP90, and HSP70 . Due to the obvious contribution to tumor survival and growth of HSPs, some HSP inhibitors were developed to cut down the thermoresistance and improve the curative effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that tumor cells can activate the cytoprotective and antiapoptotic pathways like heat shock response, thus leading to thermoresistance to oppose PTT and survive. The subsequent heat shock response could directly lead to stressful overexpression of heat shock proteins (HSPs) including HSP110, HSP90, and HSP70 . Due to the obvious contribution to tumor survival and growth of HSPs, some HSP inhibitors were developed to cut down the thermoresistance and improve the curative effect .…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent heat shock response could directly lead to stressful overexpression of heat shock proteins (HSPs) including HSP110, HSP90, and HSP70. [26][27][28] Due to the obvious contribution to tumor survival and growth of HSPs, some HSP inhibitors were developed to cut down the thermoresistance and improve the curative effect. [29,30] The Hsp90 inhibitors, 17-allylamino-17-demethoxygeldanamycin (17AAG), can specifically bind to the HSP90 ATP pocket reversibly, thus destroying its thermal-protected function potently and further leading to the death of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Hsps, especially Hsp70s are omnipresent molecular chaperones which facilitate correct protein folding and are expressed more abundantly under hyperthermia. [8] Hsp70 has also been evidenced to exert antiapoptosis effects by inhibiting caspase-3 activation and blocking kinase pathways activated by cellular stresses. [9][10][11][12] These cytoprotective effects render tumor resistant to PTT induced apoptosis.…”
Section: Doi: 101002/advs201600327mentioning
confidence: 99%
“…1A). This defines a "recovery time" between the end of HS exposure and the cytokine treatment, which is relevant to clinical hyperthermia protocols (Maluta and Kolff, 2015;Rybinski et al, 2013). In cells maintained under normal conditions, we observed a robust Ser536 p65 phosphorylation, a marker of NF-κB activity, which peaked around 15 min after TNFα stimulation ( Fig.…”
Section: Hs Modulates the Nf-κb Signalling Responses To Tnfα Stimulationmentioning
confidence: 82%
“…The ultimate goal of mathematical modelling is to interpret data and make biological predictions (Kirk et al, 2015). Here we developed and validated a dynamical mathematical model of NF-κB and HSR crosstalk, which combines previously published network structures 1 5 (Adamson et al, 2016;Rybinski et al, 2013;Szymanska and Zylicz, 2009;Zheng et al, 2016). We proposed a crosstalk mechanism to recapitulate our original data on NF-κB p65 responses in wild type and HSF1 knock-down cells as well as measurements of the IKK denaturation and activation of the HSF1-HSP pathway for a 37-43°C temperature range.…”
Section: Discussionmentioning
confidence: 99%